Cell structure and signaling - Getzenberg, Robert H. (Advances in molecular and cell biology, 1997)
In the past approximately quarter of a century, science has made significant progress in elucidating the skeletal elements of the cell, the extracellular matrix, cytoskeleton and nuclear matrix (i.e. the tissue matrix). While we currently know a great deal about some of the elements that comprise these structural systems, we still do not fully understand cellular structures and their relationship to cellular function. The cell is a highly ordered machine in which the skeleton provides the framework on which cellular functions take place. It is now becoming apparent that what were typically considered "soluble reactions" are rare, if existent at all. The structural systems contribute more to the cell than a framework for shape, although this is an important function. Cellular shape is reflecting what a cell is, does and will be. One can not inextricably separate cell structure and function, they go hand-in-hand. Numerous laboratories have contributed to our current understanding of the role of cell structure in cell signaling and we are now at an exciting time in this field. This volume summerizes where investigations into the role of the tissue matrix system in cellular signaling have come and to propose new directions that this research will take in the next several years. This is not meant to be complete, but hopefully will provide the reader with an overview on our current understanding of this field.